Propuesta de un plan estratégico de marketing para el hotel Rancho de Pecos del cantón El Guabo provincia de El Oro - Valarezo Blacio, Kely Mariel (2015)
This study has been performed in order to raise a proposal for a Strategic Marketing Plan for the Pecos Hotel Rancho El GuaboCanton, Province of El Oro The main objective is raised : will design a draft strategic marketing plan for the Hotel Rancho Pecos cantónGuabo Province of Gold and , as the following specific objectives were defined: Conduct an assessment of Rancho Pecos canton the province Guabo the Golden Set the internal factors of Hotel Rancho Pecos. Identify external factors Ranch Pecos Hotel. Create the SWOT matrix for this hotel company. Establish high-impact matrix for Pecos Ranch Hotel Canton Guabo of the province of El Oro Define strategic objectives for Pecos Ranch Hotel CantónGuabo and propose a strategic marketing plan for the Hotel Ranch Pecos Guabo Canton of the province of El Oro. The methodology involved the use of the following methods: deductive, inductive and analytic and synthetic and the following research techniques were used: observation and survey. The population considered for the development of this study is registered in the year 2012 the hotel company Pecos Ranch Canton Guabo province of El Oro thereof totaling 1878 clients and the sample is determined by 328 userscustomers. The results are presented in statistical tables with their analysis and interpretation. From this investigation it is concluded that Pecos Ranch Hotel has a Strategic Marketing Plan that allows you to perform activities based on strategic in order to fulfill the mission and vision of the business objectives. On the other hand 100% of the staff working within the Pecos Hotel Rancho El Guabo Canton province of El Oro, manifested not know the mission and vision and have not received any training course. As principal recommendation proposes that the owner manager of Pecos Hotel Rancho El Guabo Canton province of El Oro set in the present implementation of strategic marketing plan to position itself in the local and national market